2018
DOI: 10.1007/s00268-018-4872-7
|View full text |Cite
|
Sign up to set email alerts
|

Morbid Obesity’s Silver Lining: An Armor for Hollow Viscus in Blunt Abdominal Trauma

Abstract: Background Morbid obesity is usually accompanied by both subcutaneous and visceral fat accumulation. Fat can mimic an air bag, absorbing the force of a collision. We hypothesized that morbid obesity is mechanically protective for hollow viscus organs in blunt abdominal trauma (BAT). Methods The National Trauma Data Bank (NTDB) was queried for BAT patients from 2013 to 2015. We looked at the rate of gastrointestinal (GI) tract injuries in all BAT patients with different BMIs. A subset analysis of BAT patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…Arbabi et al introduced the "cushion effect" in 2003, suggesting that increased abdominal adiposity provides a "cushion" for abdominal trauma during the injury event [20]. Wang et al and Fu et al also found that obesity protects patients from severe abdominal injury [21,22]. A computational study found that an obese dummy model had increased risks for head, thorax, and lower extremity injury due to greater torso and pelvic excursions, while increased subcutaneous fat may cushion subjects from abdominal injury [23].…”
Section: Introductionmentioning
confidence: 99%
“…Arbabi et al introduced the "cushion effect" in 2003, suggesting that increased abdominal adiposity provides a "cushion" for abdominal trauma during the injury event [20]. Wang et al and Fu et al also found that obesity protects patients from severe abdominal injury [21,22]. A computational study found that an obese dummy model had increased risks for head, thorax, and lower extremity injury due to greater torso and pelvic excursions, while increased subcutaneous fat may cushion subjects from abdominal injury [23].…”
Section: Introductionmentioning
confidence: 99%
“…In a population-based cohort by Schott et al, hip fracture risk was reduced by 40% for a standard deviation increase in fat mass, while changes in lean body mass did not affect fracture rates [ 25 ]. Furthermore, Fu et al found that obese patients with blunt abdominal trauma sustained less gastrointestinal tract injuries and associated surgery [ 26 ]. These reports support the hypothesis that fat mass could aid better tolerating mechanical force incurred in trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that obesity is associated with a higher risk for posttrauma complications 4 and mortality [5][6][7] . In contrast, some studies found that obesity protects patients from severe injury 8,9 . The "Cushion Effect" was introduced by Arbabi et al in 2003 10 and suggests that increased abdominal adiposity provides a "Cushion" for abdominal trauma during the injury event.…”
Section: Introductionmentioning
confidence: 98%